2017
DOI: 10.4236/ojpm.2017.73004
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Particulate Matter from Biomass Smoke and Its Relationship to Respiratory Symptoms and Pulmonary Function among Rural Women Involved in Cassava Processing in Nigeria

Abstract: Background: Cassava processing is an important source of livelihood for many rural women and involves prolonged exposure to biomass smoke. The impact of this exposure on respiratory health of these women has not been explored. We aimed to compare the frequency of respiratory symptoms and pulmonary function among cassava processing women to that of petty traders as well as the levels of particulate matter PM 2.5 and PM 10 at the workplaces of these women. Methods: A comparative cross-sectional design. Questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…Several studies 14,15,16,17 have demonstrated an association between biomass fume exposure and the development of obstructive airway disease. One of the first associations of biomass smoke with obstructive lung disease was reported by Woolcock et al 18 in New Guinea.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies 14,15,16,17 have demonstrated an association between biomass fume exposure and the development of obstructive airway disease. One of the first associations of biomass smoke with obstructive lung disease was reported by Woolcock et al 18 in New Guinea.…”
Section: Discussionmentioning
confidence: 99%
“…Occupational exposure to wood smoke were reported in seven studies. These include charcoal production [17][18], bakery [44], fish drying [20,50], garri (cassava) processing [21] and street cooking [38].…”
Section: Sources Of Wood Smoke Exposure In Ssamentioning
confidence: 99%
“…All the seven studies on lung function [20-21, 38, 57-60] reported positive association between wood smoke exposure and reduced lung function. Three of these studies [20][21]38] reported reduced lung function [20] or higher risk of obstructive pulmonary defect [21,38] in women occupationally exposed to wood smoke. With reference to those who have worked as cassava processors for less than 10 years, working as cassava processor for more than 10 years was associated with higher risk (OR: 14.916, 95% CI: 5.077-43.820) of obstructive pulmonary defect [21].…”
Section: Respiratory Outcomesmentioning
confidence: 99%
See 2 more Smart Citations